On some China-related entries in the Oxford English Dictionary - Zhu, J (2010)
Inspired by Phil Benson's study on the relations between ethnocentrism and the China-related entries in the OED2, this paper attempts to further examine from an ideological perspective how the image of China, a so-called "peripheral object of Western knowledge", has been (mis-)constructed in the dictionary, particularly its latest 2009 CD-ROM version, into which many laudable updates, including corrections and supplements, have been meticulously incorporated, and argues that (1) although British imperialism was a turned-over page, its vestiges can still be spotted in the dictionary text, not only in the quotations, which more preserve historical information than reflect the editors' opinions, but also in the definitions and notes, which betray primarily the thoughts of none other than the editors, (2) to an average user, the OED, with its legendary philological authority, is very likely to impose "historical objectivity" on some problemtic contents and thus to mislead an innocent mind, and (3) if ethnocentrism is an unavoidable component in the OED1 and OED2, then the editorial team of the OED3 in the making would do well to introduce into their work an element of "entholocalism", by which is meant the ideological neutrality as well as the technical accuract of encyclopedic information about such important peripheral objects as China, the largest country in terms of population and one of the growing BRIC, and more relevantly here, English-learning powers in the present-day world, in the vision of the English against the backdrop of globalization, where their mother tongue has firmly established itself as the international lingua franca withour rival. So long as it is intended to remain a faithfully historical dictionary, the OED ought to advance, in the form of new editions, with the times.